GIOVANNA FOSSATI, From Grain to Pixel: The Archival Life of Film in Transition - Hackett, Yvette (Archivaria, 2012)
From Grain to Pixel: The Archival Life of Film in Transition. GIOVANNA FOSSATI. Amsterdam: Amsterdam University Press, 2009. 320 p. ISBN 978-90-8964-139-7.